Desain dan Visualisasi Kampus Universitas Diponegoro Berbasis WebGIS - Tri Adi Hermawan; Arief Laila Nugraha; Bambang Sudarsono (Departement Teknik Geodesi Universitas Diponegoro, 2014)
Diponegoro University is one of the largest university in Central Java and has a wide area location. Because of the large area makes the location of each building study program each faculty dispersed and has a considerable distance to other faculty. The availability of information about the location of each study program on campus of the University of Diponegoro was minimal. The need for information on the campus demanding the availability of information systems that are informative and provide convenience for everyone who needs information about the campus.This research using spatial data coordinates of the position and photos of objects and attribute data in the form of a campus building inventory data. Processing of panoramic images using Pano2VR software while the coordinate data collection using GPS handheld. Maps are used utilizing Google Earth and Google Maps then developed using HTML website framework., MySQL with phpMyAdmin features used as database. Data that has been acquired is then processed using the software and information presented in a campus-based WebGIS.The final result of this research is the application of Diponegoro University campus map-based WebGIS equipped with information of each faculty, studi program, Unit contained in the University of Diponegoro and there are panoramic images to look around the location we were looking for.Keywords: Diponegoro University, campus maps, webGIS